Implementation Of A Waste Bank Management Program In The South Tangerang City Area (Study In Benda Baru Subdistrict) - Susanto; Riau, Dwi Putranto; Budiati, Ayuning (Sinergi International Journal of Law, 2024)
This research aims to analyze the implementation of the waste bank management program and the waste bank management model in Benda Baru Subdistrict, South Tangerang City. This research uses a qualitative approach, data collection techniques using observations, in-depth interviews, Focus Group Discussions (FGD) and documentation. The sampling technique used in this research was purposive sampling. The informants consisted of 5 groups of informants, namely the Environmental Service, Village Employees, Waste Bank Managers, Environmental Monitoring Institutions and the Community of Banda Baru Village, South Tangerang City. This research uses the Miles and Huberman Model Qualitative Data Analysis Technique where the implementation of the waste bank management program uses policy implementation theory from George C. Edwards III, namely four variables in public policy, namely Communication, Resources, attitudes (dispositions or attitudes) and bureaucratic structure and Van Horn Theory. The latest in this research is the collaboration between the use of information technology and public policy regarding waste bank management. Waste bank management model to implement a waste bank management program by including information technology elements in the information flow, sorting/sorting flow, bookkeeping flow and customer deposit distribution flow at the waste bank. Meanwhile, the model for implementing the waste bank management program in the flow of collecting or purchasing waste from local government waste banks requires establishing a Regional Owned Enterprise or regional company that specifically handles waste produced from waste banks. This has a massive impact on the green economy concept to improve community welfare.